RESEÑA : Gavara de Cara, Juan Carlos. Contenido y función del termino de comparación en la aplicación del principio de igualdad. Thomson Aranzadi, 2005 - Giménez Gluck, David (Teoría y Realidad Constitucional, 2007)
The review comments the first monograph dedicated exclusively to the term of comparison in Spain, Contenido y Función del Término de Comparación en la Aplicación del Principio de Igualdad, by Juan Carlos Gavara de Cara. The concept of term of comparison used by the author, the differences between the diverse tests of equality developed by the Spanish Constitutional Court, the analysis of the structure of the term of comparison, divided in three phases. All of these items, among others, are commented critically in this review, trying not just to agree or criticise but also contributing with own ideas to the debate.